2014
DOI: 10.1128/aac.02496-13
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib and Tofacitinib Are Potent and Selective Inhibitors of HIV-1 Replication and Virus ReactivationIn Vitro

Abstract: The JAK-STAT pathway is activated in both macrophages and lymphocytes upon human immunodeficiency virus type 1 (HIV-1) infection and thus represents an attractive cellular target to achieve HIV suppression and reduced inflammation, which may impact virus sanctuaries. Ruxolitinib and tofacitinib are JAK1/2 inhibitors that are FDA approved for rheumatoid arthritis and myelofibrosis, respectively, but their therapeutic application for treatment of HIV infection was unexplored. Both drugs demonstrated submicromola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 35 publications
4
71
2
2
Order By: Relevance
“…Gavegnano et al . reported that ruxolitinib and tofacitinib, two inhibitors with selectivity for subtypes JAK1/2 can potently inhibit viral reactivation in vitro [96]. This suggests that in addition to their direct anti-inflammatory effects, these molecules may also directly act on the virus life cycle, and like dCA, may prevent residual levels of viral production from the reservoir.…”
Section: Clinical Interventions: Breaking the Vicious Circlementioning
confidence: 99%
“…Gavegnano et al . reported that ruxolitinib and tofacitinib, two inhibitors with selectivity for subtypes JAK1/2 can potently inhibit viral reactivation in vitro [96]. This suggests that in addition to their direct anti-inflammatory effects, these molecules may also directly act on the virus life cycle, and like dCA, may prevent residual levels of viral production from the reservoir.…”
Section: Clinical Interventions: Breaking the Vicious Circlementioning
confidence: 99%
“…A prospective clinical trial is being developed to evaluate this concept further. Other drugs that would limit T cell activation, including those that inhibit the JAK/STAT pathway (76), are also being developed. As chronic inflammation may contribute to excess morbidity in ART-suppressed, HIV-1-infected individuals (9), a number of therapies that target the inflammatory pathways are being developed as adjuncts to therapy (e.g., methotrexate, anti-fibrotic drugs, anti-CMV therapy, and a number of agents aimed at gut mucosa and microbial translocation).…”
Section: Immune Modulating Drugsmentioning
confidence: 99%
“…Thus, inhibition of the JAK-STAT signaling pathway will inhibit HIV replication. In agreement with this, JAK inhibitors were recently reported to inhibit HIV replication in peripheral blood mononuclear cells (PBMCs) and macrophages (54,55). In contrast to many other viral infections, the activation of the immune system cannot easily inhibit HIV spread within a host.…”
Section: Figmentioning
confidence: 65%